Community Development of Tourism Interest Group Malang Regency as an Effort to Optimize Tourism - Kusumawati, Yudhistya Ayu; Lasmy, Lasmy; Gasa, Frederik Masri; Renanda, Daud Gezha (Bina Nusantara University, 2024)
The Covid-19 pandemic has had a significant impact on the economy Indonesia, especially for the tourism sector. This sentence highlights the importance of tourism to the government. Based on the situation analysis, Malang Regency has an area marine tourism located in South Malang. One of them is the Bowele tourist area. Bowele which consists of a group of beaches (Bolu-bolu, Wedi Awu, and Lenggoksono) is a potential coastal tourism area in Malang Regency. Apart from its stunning natural beauty, the area also boasts significant economic potential in marine products, this tour is also a venue for large-scale surfing activities international. However, this area has not been optimally developed by tourism managers represented by the Boele Tourism Awareness Group (Pokdarwis), including resource management human resources, finance, marketing, and distribution. So, this community service activity highlighted critical deficiencies in business management as well as marketing management. Community service through the Community Partnership Program is designed to enact branding that encourages digital marketing activities including applications/ website and social media content as an effort to digitize and optimize tourist areas Bowele Beach. The proposed service activity stems from research conducted by the proposing team's lecturers in an earlier period. During this community service project, the team helps partners develop skills to implement applications/websites and publications through social media content through counseling and mentorship. In addition, assistance and training related to business management aspects. This community service plays a vital role in empowering tourism businesses to leverage social media for marketing and distributing their offerings. It’s hoped this community service project will boost tourism and keep it going even during and after the pandemic.